Pentahelix Synergy in Post-Tsunami Disaster Recovery to Support Community Resilience in Facing Disaster in Pandeglang Regency - Kurniadi, Anwar; Syamsunasir, Syamsunasir; Widana, I Dewa Ketut Kerta (Technium Social Sciences Journal, 2023)
The pentahelic synergy must be carried out by the Pandeglang Regency to speed up the recovery process after the tsunami disaster. If it doesn’t work, it will disrupt the resilience of the community in facing the coming disaster. This study used a qualitative descriptive design method. The purpose of this study was to analyze how far the pentahelic synergy in post-tsunami recovery is to support community resilience in facing disasters in Pandeglang Regency. The research was conducted at Carita Beach, Labuan, Panimbang and Sumur of Pendeglang Regency with 16 informants. The research data were analyzed in four steps. The results showed that the implementation of pentahelic synergy carried out by BPBD Pandeglang Regency in achieving post-tsunami recovery was in the good or effective category. and community resilience in dealing with disasters is in a strong position. The conclusion is that the effect of pentahelic synergy is able to increase the resilience of the community which is dominated by psychological and social aspects, so that it will tend to lead to the strengthening of the existing religious culture that supports government programs